Full-face ALA-PDT for facial actinic keratosis: Two case reports - Wenjing Zha; Jianhua Huang; Ting Lyu; Fei Miao; Minfeng Wu; Jie Shen; Rongyi Zhu; Hongwei Wang; Lei Shi (Photodiagnosis and Photodynamic Therapy)
We reported two cases of full-face 5-aminolevulinic acid-photodynamic therapy (ALA-PDT) for facial multiple actinic keratosis (AK). After the full-face ALA-PDT, we observed that the AK lesions on the faces of the patients were completely cleared and facial rejuvenation was achieved. In our follow-up, one patient was free of recurrence for over 13 months and the other one for over 28 months. The experience of these two cases may indicate that full-face ALA-PDT has an excellent therapeutic effect while potentially preventing the recurrence of AK.